Creep performance evaluation of Cold Mix Asphalt patching mixes (2023)
Cold Mix Asphalt (CMA) is commonly used in lieu of typical Hot Mix Asphalt (HMA) for localized pavement patching due to the quantities, intermittent locations and times when repairs need to be executed.